PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T.; Chamberlain, John H. (The Accounting Review, 1959)
The article focuses on various problems, which were prepared by the Board of Examiners of the American Institute of Certified Public Accountants (CPA) and were presented as the second half of the CPA examination in accounting practice on May 14, 1959. The suggested time allowance for each question is also given in the article. In one question, details of a Washington D.C.-based hypothetical company namely Y & P Music Co., which operates two retail music stores, one located in Seattle, Washington State and the other in Tacoma, Washington State is provided. The examinee is required to adjust entries to be recorded on each set of books correcting the account balances in the question. In another question, the estimated balance sheet of a hypothetical company the Claxton Machine Co. Inc. is provided. Claxton Machine Co. Inc. maintains and supplies the raw materials for machines, which it rents out on one-year contracts. The charge for service and supplies is billed monthly and is based on usage, $8 for each 100 units as measured by meters with a minimum monthly charge of $160 per machine.